Single Nucleotide Polymorphism in the IL17A Gene Is Associated with Interstitial Lung Disease Positive to Anti-Jo1 Antisynthetase Autoantibodies - Marco Antonio Ponce-Gallegos; Montserrat I. González-Pérez; Mayra Mejía; Karol J. Nava-Quiroz; Gloria Pérez-Rubio; Ivette Buendía-Roldán; Espiridión Ramos-Martínez; Jorge Rojas-Serrano; Ramcés Falfán-Valencia (Life, 2021)
Antisynthetase syndrome (ASSD) is a rare multisystemic connective tissue disease affecting the skin, joints, muscles, and lungs, characterized by anti-aminoacyl transfer-RNA-synthetases (anti-tRNA) autoantibodies production, being anti-Jo1 the most frequent. We included one-hundred twenty-one ASSD patients and 340 healthy subjects (HS), and also, we divided the case group into anti-Jo1 and non-anti-Jo1. Two single nucleotide polymorphisms (SNPs) in the IL17A gene were evaluated. Anti-Jo1 was the most common anti-tRNA antibody in our cohort, and the most frequent tomographic pattern was non-specific interstitial pneumonia (NSIP). Anti-Jo1 ASSD patients had higher levels of creatine phosphokinase than the non-anti-Jo1 group. Significant differences in genotype frequencies with rs8193036/CC between anti-Jo1 vs. non-anti-Jo1 ASSD patients (p < 0.001), maintaining the association after Bonferroni correction (p = 0.002). Additionally, in the anti-Jo1 group vs. HS comparison, we found a statistically significant difference with the same SNP (p = 0.018, OR = 2.91, 95% CI = 1.15–7.35), maintaining the association after Bonferroni correction (p = 0.036). The rs8193036/CC genotype in IL17A is associated with ASSD patients with anti-Jo1. Also, anti-Jo1 and non-anti-Jo1 patients display differences in genotype frequencies.